TRACE ELEMENT ABUNDANCES AND MAGNESIUM, CALCIUM, AND TITANIUM ISOTOPIC COMPOSITIONS OF GROSSITE-CONTAINING INCLUSIONS FROM THE CARBONACEOUS CHONDRITE ACFER 182 - Weber D.; Bischoff A.; Zinner E. (My University, 1995)
The carbonaceous chondrite Acfer 182 contains Ca,Al-rich inclusions (CAIs) that differ from most CAIs in other meteorites. Many of them contain grossite (CaAl4O7), whose modal abundance exceeds 30 vol % in most of these CAIs (“grossite-rich inclusions”). Similar inclusions have been found only in the CH chondrite ALH85085 and the CR chondrite Acfer 059-El Djouf 001. Ion microprobe analyses of trace elements were made on nineteen CAIs from Acfer 182 and two CAIs from Acfer 059-El Djouf 001, of Al-Mg isotopes on eighteen Acfer 182 and the two Acfer 059-El Djouf 001 inclusions, and of calcium isotopes on ten Acfer 182 inclusions (on six of them also of titanium isotopes) and one Acfer 059-El Djouf 001 inclusion.